Genetic assessments, dominance estimates of economic traits of gynoecious cucumber (Cucumis sativus) under Himalayas - TYAGI, NIDHI; SHARMA, H R; DOGRA, R K; GUPTA, MEENU (The Indian Journal of Agricultural Sciences, 2023)
In India generally monoecious and cross-pollinated cucumber (Cucumis sativus L.) hybrids/varieties are grown. The use of stable gynoecious cucumber varieties/hybrids would increase the productivity of cucumber in India. In the past, despite improvement in monoecious cucumber varieties/hybrids, little effort has been done into the development of stable gynoecious hybrids. To address this issue 3 genetically diverse gynoecious lines and improvement, and 6 testers were crossed in line × tester fashion to develop 18 crosses during 2017. These 18 crosses along with 9 parents evaluated at the Krishi Vigyan Kendra, Kandaghat, Himachal Pradesh and Dr. YSPUHF, Solan, Himachal Pradesh during pre-kharif season 2018–19 to determine the mode of gene action, combining ability, extent heterosis and potence ratio for 12 quantitative traits. Experimental results depicted that the dominant component of variance (σ2S) was found higher than the additive component of variance (σ2S) for all the traits indicating a predominant role of non-additive gene action governing yield and its contributing traits during both the years. Gynoecious inbred lines KTG-40, 2870G and testers K-90, UHF-16 were found most promising general combiners for fruit yield. The cross combination KTG-40 × K-90 and 2870G × K-90 isolated based on heterosis manifested and SCA effects. Further, the performance of top 7 heterotic crosses illustrate the presence of overdominance in most of the crosses for traits under study, suggesting the importance of heterosis breeding for the development of early, high-yielding, disease tolerance stable gynoecious hybrids in cucumber.